Nivel de conocimiento sobre autocuidado en adultos mayores. Grupo Jubilados. San Miguel de Bolívar. Periodo noviembre 2022 -abril 2023 - Arboleda Mantilla, Adriana Nashely (2023)
ABSTRACT Self-care is a fundamental aspect of maintaining good health and well-being in old age. In this sense, it is important to evaluate the level of knowledge about self-care in older adults. The objective of the following research is to determine the level of knowledge about self-care in older adults. Retired group. San Miguel de Bolivar. Period November 2022 - April 2023. For this purpose, a quantitative research of descriptive scope was applied, with a quasi-experimental field and cross-sectional design, working with a population of 35 retired adults to whom a closed questionnaire was applied. The results of the survey indicate that 29% of the older adults do not engage in physical activity. However, 43% maintain harmful habits, such as tobacco and alcohol consumption. In addition, a significant portion of older adults forget to take their medications and a portion do not regularly attend scheduled appointments. In terms of eating habits, most older adults have a varied diet, but with some deficiencies in terms of dairy, nuts, and vegetable and greens intake. This can have a negative impact on their long-term health. Importantly, the importance of self- care varies among participants, with only one-third considering it very important. Many of the older adults surveyed need help getting around and have problems with balance and falls, which increases their vulnerability to injury and affects their quality of life and independence. In conclusion, the survey results indicate that retirees in San Miguel de Bolivar have a level of knowledge about self-care that needs to be improved. It is necessary to provide support and resources to improve knowledge about their disease and increase the importance of self-care in older adults. In addition, it is important to consider the mobility and balance needs of older adults to prevent injuries and improve their quality of life Key words: Elderly, self-care, knowle